2013
DOI: 10.1109/tasl.2012.2215591
|View full text |Cite
|
Sign up to set email alerts
|

An Unsupervised Approach to Cochannel Speech Separation

Abstract: Abstract-Cochannel (two-talker) speech separation is predominantly addressed using pretrained speaker dependent models. In this paper, we propose an unsupervised approach to separating cochannel speech. Our approach follows the two main stages of computational auditory scene analysis: segmentation and grouping. For voiced speech segregation, the proposed system utilizes a tandem algorithm for simultaneous grouping and then unsupervised clustering for sequential grouping. The clustering is performed by a search… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In addition to the above comparisons, we have compared with Hu and Wang (2013), where a clustering algorithm is used to group short pitch contours into two speakers. We found that this method performs better than Jin and Wang's method, but worse than the speaker-dependent method by Wohlmayr et al The details of this comparison can be found in Liu and Wang (2015b).…”
Section: Results and Comparisonsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the above comparisons, we have compared with Hu and Wang (2013), where a clustering algorithm is used to group short pitch contours into two speakers. We found that this method performs better than Jin and Wang's method, but worse than the speaker-dependent method by Wohlmayr et al The details of this comparison can be found in Liu and Wang (2015b).…”
Section: Results and Comparisonsmentioning
confidence: 99%
“…Although most speaker-independent models perform well for estimating pitch periods, they can not assign pitch estimates to the underlying speakers for multipitch tracking. To alleviate this problem, Hu and Wang (2013) build their system on the tandem algorithm (Hu and Wang, 2010) and group simultaneous pitch contours into two speakers using a constrained clustering algorithm. Similarly, Duan et al (2014) take the pitch estimates of speaker-independent multipitch trackers as input and stream pitch points by clustering.…”
Section: Introductionmentioning
confidence: 99%